Targeting TLR Signaling Cascades in Systemic Lupus Erythematosus and Rheumatoid Arthritis: An Update - George D. Kalliolias; Efthimia K. Basdra; Athanasios G. Papavassiliou (Biomedicines, 2024)
Evidence from animal models and human genetics implicates Toll-like Receptors (TLRs) in the pathogenesis of Systemic Lupus Erythematosus (SLE) and Rheumatoid Arthritis (RA). Endosomal TLRs sensing nucleic acids were proposed to induce lupus-promoting signaling in dendritic cells, B cells, monocytes, and macrophages. Ligation of TLR4 in synovial macrophages and fibroblast-like synoviocytes (FLSs) by endogenous ligands was suggested to induce local production of mediators that amplify RA synovitis. Inhibition of TLRs using antagonists or monoclonal antibodies (mAbs) that selectively prevent extracellular or endosomal TLR ligation has emerged as an attractive treatment strategy for SLE and RA. Despite the consistent success of selective inhibition of TLR ligation in animal models, DV-1179 (dual TLR7/9 antagonist) failed to achieve pharmacodynamic effectiveness in SLE, and NI-0101 (mAb against TLR4) failed to improve arthritis in RA. Synergistic cooperation between TLRs and functional redundancy in human diseases may require pharmacologic targeting of intracellular molecules that integrate signaling downstream of multiple TLRs. Small molecules inhibiting shared kinases involved in TLR signaling and peptidomimetics disrupting the assembly of common signalosomes (“Myddosome”) are under development. Targeted degraders (proteolysis-targeting chimeras (PROTACs)) of intracellular molecules involved in TLR signaling are a new class of TLR inhibitors with promising preliminary data awaiting further clinical validation.